Evaluation of polyculture of Indian major carps in periphyton-based ponds - Azim, M. Ekram; Verdegem, Marc C.J.; Rahman, Mohammad Mustafizur; Wahab, Md Abdul; Van Dam, Anne A.; Beveridge, Malcolm C. M (Elsevier B.V., 2002)
Production of three Indian major carps, catla Catla catla, rohu Labeo rohita and kalbaush L. calbasu, in a periphyton-based polyculture system was compared. Bamboo poles, approximating a submerged surface area equal to the total pond surface area, were used as substrates for periphyton and were planted vertically into the pond bottom. Ponds were fertilized fortnightly with 4500 kg cow manure, 150 kg urea and 150 kg triple super phosphate (TSP) per hectare. Four stocking combinations were applied: 60% rohu plus 40% catla with a total stocking density of 10000 ha-1 (treatment CR), CR plus 15% kalbaush (C15), CR plus 30% kalbaush (C30) and CR plus 45% kalbaush (C45). A treatment with 60% rohu plus 40% catla without bamboo substrate was used as control (CR0). Treatments differed significantly in some water quality parameters (Secchi depth, total alkalinity, orthophosphate, total ammonia and chlorophyll a) and periphyton biomass (dry matter (DM), ash-free dry matter (AFDM) and ash content). The ash (15–19%), protein (23–26%) and energy (19–20 kJ g -1) contents of the estimated periphyton can be considered as broadly appropriate to fish dietary needs. The relative contributions of algae to the periphytic biomass were 30–60% depending on the treatment. In total, 50 genera of algae, 13 genera of zooplankton and some macrobenthic invertebrates were identified from the periphyton samples. Survival of rohu and catla was higher in ponds with bamboo poles than in the controls. Net fish yields of the three species were found to be higher in treatment C15. Highest total fish yield, over a 90-day culture period, was recorded in treatment C15 (2306 kg ha-1) followed by treatment C45 (1914 kg ha-1), treatment CR (1652 kg ha-1), treatment C30 (1507 kg ha-1) and treatment CR0 (577 kg ha-1). Fish production from the periphyton-based system was 2.8 times higher than that of the control. The addition of 15% kalbaush (i.e. a stocking ratio of 12:8:3 rohu–catla–kalbaush) at a total stocking density of 11500 juveniles ha-1 resulted in a further 40% increase in production and is an appropriate combination in a periphyton-based polyculture system. The stable nitrogen and carbon isotopes ratio indicated that rohu grazed on periphyton, whereas catla depended on planktonic food organisms.